A REVIEW POTENSI DAUN SEMBUNG (Blumea balsamifera (Lin.) DC) SEBAGAI AGEN ANTIKANKER PAYUDARA - Diah Ayu Aguspa Dita, S.Kep, Ners, M.Biomed; Risti Dwi Ocktaviani; Maeike Grestiana Sinaga; Dwiani Ratna Sari (ALOTROP, 2023)
Breast cancer is the leading cause of death in women caused by the development of abnormal cells in the breast that continue to multiply. Current cancer therapy is surgery, radiation and/or chemotherapy. Breast cancer therapy currently being carried out can cause various side effects. One of the natural ingredients that have the potential as anticancer is Sembung (Blumea balsamifera) leaves. This journal review aims to provide information about the effect of giving Sembung leaf herbal tea (Blumea balsamifera) on breast cancer. This paper is the result of a review in June 2021-June 2022 using the design of this study is a literature review. Search publication articles on PubMed, google scholar, elsevier, science direct, PMC, Cochrane, Nature, and EBSCO using selected keywords, namely: active compound content in Blumea balsamifera, breast cancer, anticancer using keywords selected based on PICO. The results of various information prove that Sembung leaves have excellent potential in inhibiting cell growth, where Sembung leaves contain dihydroflavonol, luteolin-7-methyl ether, bioflavonoids, L-borneol, and essential oils. The mechanism of sembung leaf as an anticancer agent is by suppressing cancer cell proliferation, inducing apoptosis, inhibiting the P-GP efflux pump, and inhibiting cancer cell angiogenesis. How to use sembung leaves as an anticancer agent, namely: preparation of tools and materials, determination of plants, taking sembung leaves, extracting simplicia, and dissolving in water with an unknown concentration. Side effects that arise from the use of sembung leaves are itching and skin irritation. Keywords: Blumea balsamifera, Breast Cancer, Anticancer